If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -1(7) = 17 Multiply -1 * 7 3b + -7 = 17 Reorder the terms: -7 + 3b = 17 Solving -7 + 3b = 17 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3b = 17 + 7 Combine like terms: -7 + 7 = 0 0 + 3b = 17 + 7 3b = 17 + 7 Combine like terms: 17 + 7 = 24 3b = 24 Divide each side by '3'. b = 8 Simplifying b = 8
| 2m^2+10=10 | | 4+5*(x+2)=3-x | | 1=.08(Y^1) | | -2a-3=-15 | | -1/4(x-8)+1/2(x+2)=-3 | | -2u+8=4 | | -3x-2=84 | | 2a-5=-3 | | (5-7xy+8x^2-y^2)-(3y^2-7xy-6)= | | 3c-3=27 | | 14a=-1+13a | | 3a-(-4)=7 | | -2(x+1)-(8+7x)=-10x | | -2v+9=27 | | 2a-(-8)=18 | | -3c-9=-15 | | -3c-4=-7 | | -3z+1=-26 | | J-17=7 | | -2y+2=26 | | 10a+18=8a+4 | | -2z-1=9 | | x*x*x-3X*X*X*X*X*X+X= | | 4x+(2-3x)=20 | | -3u-2=13 | | 10=-16x^2+12x | | 4x+2-3x=20 | | 75=0.25x+x | | y=-x^2+12x-4 | | 5+m/4=5 | | -12=(-x)-(2) | | 16x^2+48x+160=0 |